AtPER1 enhances primary seed dormancy and reduces seed germination by suppressing the ABA catabolism and GA biosynthesis in Arabidopsis seeds. (22nd October 2019) - Chen, Huhui; Ruan, Jiuxiao; Chu, Pu; Fu, Wei; Liang, Zhenwei; Li, Yin; Tong, Jianhua; Xiao, Langtao; Liu, Jun; Li, Chenlong; Huang, Shangzhi
Summary: Seed is vital to the conservation of germplasm and plant biodiversity. Seed dormancy is an adaptive trait in numerous seed‐plant species, enabling plants to survive under stressful conditions. Seed dormancy is mainly controlled by abscisic acid (ABA) and gibberellin (GA) and can be classified as primary and secondary seed dormancy. The primary seed dormancy is induced by maternal ABA. Here we found that AtPER1, a seed‐specific peroxiredoxin, is involved in enhancing primary seed dormancy. Two loss‐of‐function atper1 mutants, atper1‐1 and atper1‐2, displayed suppressed primary seed dormancy accompanied with reduced ABA and increased GA contents in seeds. Furthermore, atper1 mutant seeds were insensitive to abiotic stresses during seed germination. The expression of several ABA catabolism genes ( CYP707A1, CYP707A2, and CYP707A3 ) and GA biosynthesis genes ( GA20ox1, GA20ox3, and KAO3 ) in atper1 mutant seeds was increased compared to wild‐type seeds. The suppressed primary seed dormancy of atper1‐1 was completely reduced by deletion of CYP707A genes. Furthermore, loss‐of‐function of AtPER1 cannot enhance the seed germination ratio of aba2‐1 or ga1‐t, suggesting that AtPER1‐enhanced primary seed dormancy is dependent on ABA and GA. Additionally, the level of reactive oxygen species (ROS) in atper1 mutant seeds was significantly higher than that in wild‐type seeds. Taken together, our results demonstrate that AtPER1 eliminates ROS to suppress ABA catabolism and GA biosynthesis, and thus improves the primary seed dormancy and make the seeds less sensitive to adverse environmental conditions. Significance Statement: Loss‐of‐function of AtPER1 (a 1‐cysteine peroxiredoxin) enhances seed germination and reduces primary seed dormancy and seed sensitivity to adverse environment. AtPER1 suppresses the transcription of ABA catabolism genes and promotes the transcription of GA biosynthesis genes by detoxifying ROS in Arabidopsis seeds.